The Five Nations model for prison health surveillance: lessons from practice across the UK and Republic of Ireland. (15th November 2019) - Perrett, S; Plugge, E; Conaglen, P; O'Moore, E; Sturup-Toft, S
ABSTRACT: Background: Prison populations experience an increased burden of physical, mental and social health needs compared to the community, further impacted by the prison environment. Surveillance systems to monitor health and well-being trends in prisons are lacking, presenting a challenge to services planners, and policy makers who often lack evidence to inform decisions. Method: The Five Nations Health and Justice Collaboration, a body of experts on prison health across the UK and Republic of Ireland (ROI), met to share and discuss challenges and opportunities to developing robust prison health surveillance systems that could inform local provision, guide national policy and enable cross-border comparisons. Results: Challenges to robust prison health surveillance systems were shared across the UK and ROI. Methods of surveillance differed across nations and included performance indicators and outcome measures as part of local or national programs. All nations had strong public health infectious disease notification systems. Conclusions: The Five Nations Health and Justice Collaboration is proposing a new model for prison health surveillance, based on established guidelines for public health surveillance but with additional features that recognize the uniqueness of the prison environment and need for a whole prison approach, built on collaboration and sharing of data between health and justice sectors.